Fish Feeding and Solar Panel Technology Implementation for the Jatiluhur Reservoir Community of Floating Net Cages Farmers - Wahyu Adhie Candra; Nuryanti; Sarosa Castrena Abadi; Muhammad Nursyam Rizal (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The Implementation of Fish Feed Technology and Solar Panels is geared towards enhancing fish farming productivity in the Jatiluhur Dam community, village of Kertamanah, Purwakarta, where substantial potential awaits but technological support is lacking. Fish farmers grapple with formidable challenges in the feeding process, including uncontrollable, uneven, and immeasurable feed distribution, resulting in a high mortality rate among the fish. To address these challenges, Community Service (PKM) activities were undertaken, involving the design of an innovative fish feed dispenser with a capacity of 20-30 kg using automatic fish feeder technology. Local partners also underwent intensive training on tool usage, maintenance, and repair. The outcomes reveal that partners can autonomously control feed dispensing through timers on control panels, utilizing remote controls, and determining feeding durations. A significant emphasis of this research lies in the incorporation of solar panels, strategically implemented to power the automatic fish feeder system. This addition enables flexible settings for feeding duration and frequency, facilitated by the integration of a timer and a remote controller for distance control. This solar panel implementation is particularly crucial due to the constraints posed by the Floating Net Cage positioned in the center of the dam. Anticipated benefits encompass heightened efficiency in fish feeding management, a reduction in fish mortality rates, and the fortification of sustainable fish farming productivity. Additionally, the integration of solar panels addresses the energy needs of the system, offering an environmentally friendly alternative in the face of restrictions posed by the cage's location. This research significantly contributes to advancing sustainable fisheries business models, effectively harnessing modern technology within the fisheries sector, and laying the groundwork for innovative policies and practices in the future.